11. Five Lieder for Medium Voice and Piano, Op. 1 by Mihail Jora - Stylistic-Interpretive Considerations - Petrescu Cezara Florentina (Sciendo, 2021)
Mihail Jora, "the father" of modern Romanian lied, consistently composed vocal miniatures for voice and piano between 1914 and 1968, permanently refining the appearance and content of this group of works that became representative for Romanian music. He began his journey in the first decades of the XX-th century, when, in Romania, the vocal-chamber musical genre had just begun its rapid evolution and synchronization with European trends, creatively capitalizing on the influence of already established composers. The visible transformation took place not only through the creative assimilation of formal patterns and the way music was "made", but also trough the choice of poems. Five lieder for medium voice and piano [Fünf Lieder für eine Mittelstimme] op.1 on german lyrics is the work we will submit to stylistic-interpretive analysis to show both its uniqueness and its contact surfaces with the German lied and with Jora's mature creation.